Effects of the clinical education program led by a clinical nurse educator on nursing practice readiness, transition shock, and education satisfaction for newly graduated nurses - Dohyun Hwang; Yeonjin Kim; Yong Eun Kwon; Sujin Shin (The Journal of Korean Academic Society of Nursing Education, 2026)
Purpose: This study evaluated the effects of a 12-week clinical education program led by a clinical nurse educator (CNE) on newly graduated nurses’ nursing practice readiness, transition shock, and education satisfaction based on Kirkpatrick’s model.Methods: A nonequivalent control group pretest–posttest design was employed. Participants were newly graduated nurses hired at a university hospital in Seoul between August 2024 and May 2025. The experimental group (n=26) received the CNE-led program in addition to usual preceptorship, while the control group (n=26) received only preceptorship. While nursing practice readiness, transition shock, and education satisfaction were measured post-intervention, nursing practice readiness was also measured pre-intervention.Results: Education satisfaction was significantly higher in the experimental group than in the control group. Although the between-group difference in overall nursing practice readiness was not statistically significant, nursing practice readiness increased within the experimental group. Subdomain analyses revealed greater improvements in patient-centeredness, self-regulation, and collaborative interpersonal relationships within the experimental group than within the control group. Regarding transition shock, the experimental group reported significantly better coworker relationships than did the control group.Conclusion: The CNE-led clinical education program improved education satisfaction and strengthened selected components of nursing practice readiness. However, its effects on transition shock were mixed; no significant difference was observed in the overall score, and subscale findings were divergent in direction.